Development and testing of AAV-delivered single-chain variable fragments for the treatment of methamphetamine abuse. - Charles E Hay; Guillermo A Gonzalez; Laura E Ewing; E Elizabeth Reichard; Michael D Hambuchen; Nisha Nanaware-Kharade; Sinthia Alam; Chris T Bolden; S Michael Owens; Paris Margaritis; Eric C Peterson (PLoS ONE)
Methamphetamine (METH) substance abuse disorders have major impact on society, yet no medications have proven successful at preventing METH relapse or cravings. Anti-METH monoclonal antibodies can reduce METH brain concentrations; however, this therapy has limitations, including the need for repeated dosing throughout the course of addiction recovery. An adeno-associated viral (AAV)-delivered DNA sequence for a single-chain variable fragment could offer long-term, continuous expression of anti-METH antibody fragments. For these studies, we injected mice via tail vein with 1 x 10(12) vector genomes of two AAV8 scFv constructs and measured long-term expression of the antibody fragments. Mice expressed each scFv for at least 212 days, achieving micromolar scFv concentrations in serum. In separate experiments 21 days and 50 days after injecting mice with AAV-scFvs mice were challenged with METH in vivo. The circulating scFvs were capable of decreasing brain METH concentrations by up to 60% and sequestering METH in serum for 2 to 3 hrs. These results suggest that AAV-delivered scFv could be a promising therapy to treat methamphetamine abuse.